2011
DOI: 10.1088/0004-637x/743/2/170
|View full text |Cite
|
Sign up to set email alerts
|

OBSERVATIONS OF ENERGETIC HIGH MAGNETIC FIELD PULSARS WITH THEFERMILARGE AREA TELESCOPE

Abstract: We report the detection of γ-ray pulsations from the high-magnetic-field rotation-powered pulsar PSR J1119−6127 using data from the Fermi Large Area Telescope. The γ-ray light curve of PSR J1119−6127 shows a single, wide peak offset from the radio peak by 0.43 ± 0.02 in phase. Spectral analysis suggests a power law of index 1.0 ± 0.3 +0.4 −0.2 with an energy cut-off at 0.8 ± 0.2 +2.0 −0.5 GeV. The first uncertainty is statistical and the second is systematic. We discuss the emission models of PSR J1119−6127 an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 83 publications
4
40
0
Order By: Relevance
“…In its normal rotation-powered state, PSRJ1119-6127 has a single-peaked pulse profile at 1.4 GHz (Camilo et al 2000) that is aligned with a single-peaked (Gonzalez et al 2005) broad profile in the 0.5-2 keV emission band, which is consistent with thermal emission from the polar cap. In γ-rays, PSRJ1119-6127 also shows a single-peaked profile consistent with outer gap emission (Parent et al 2011). Our observation of multicomponent emission at S-band shortly after the outburst is indicative of a more complex emission geometry and possibly non-dipolar field components near the neutron star surface.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In its normal rotation-powered state, PSRJ1119-6127 has a single-peaked pulse profile at 1.4 GHz (Camilo et al 2000) that is aligned with a single-peaked (Gonzalez et al 2005) broad profile in the 0.5-2 keV emission band, which is consistent with thermal emission from the polar cap. In γ-rays, PSRJ1119-6127 also shows a single-peaked profile consistent with outer gap emission (Parent et al 2011). Our observation of multicomponent emission at S-band shortly after the outburst is indicative of a more complex emission geometry and possibly non-dipolar field components near the neutron star surface.…”
Section: Discussionsupporting
confidence: 50%
“…PSRJ1119-6127 was initially discovered in the Parkes multibeam pulsar survey (Camilo et al 2000) and is likely associated with the Galactic supernova remnant G292.2-0.5 (Crawford et al 2001) at a distance of 8.4 kpc (Caswell et al 2004). This pulsar has been detected in X-rays (Gonzalez & Safi-Harb 2003) and gamma-rays (Parent et al 2011), and it is also known to glitch (Weltevrede et al 2011). Unusual pulse profile changes, short radio bursts, and irregular timing recoveries (Weltevrede et al 2011;Antonopoulou et al 2015) have been observed following a glitching event.…”
Section: Introductionmentioning
confidence: 96%
“…In young radio pulsars like PSR J1119-6127, hard X-ray emission is thought to arise in the context of outer-gap models (e.g., Wang et al 2013) from synchrotron radiation from secondary electron/positron pairs produced by inward propagating curvature radiation γ-rays. As discussed by Parent et al (2011), in PSR J1119-6127, the X-ray/γ-ray phase offset, together with the single-peak morphology of the γ-ray pulse, are well explained in outer-gap models. The luminosity of both the X-ray and γ-ray emission in this picture must be bounded by the spin-down power.…”
Section: Discussionmentioning
confidence: 80%
“…Including the flux from 10 keV extrapolated to the top of the NuSTAR band increases this value by ∼20%. The efficiency for conversion of Ė to Fermi-band γ-ray emission, at least in quiescence, was estimated by Parent et al (2011) to be 0.23. With a comparable amount of energy suddenly appearing in X-rays, the Fermi-band emission may have been affected during this outburst.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence of pulsations was detected above 2.5 keV (Ng et al 2012). Gamma-ray pulsations were reported from PSR J1119-6127 using Fermi, making it the source with the highest inferred B-field detected among γ-ray pulsars (Parent et al 2011).…”
Section: Introductionmentioning
confidence: 89%